Implementation of Intensive Qur’an Recitation (Tahsin) Instruction to Improve Qur’an Reading Skills at SDIT Baitul Muslim in East Lampung2025/2026 School Year - Sri Rahayu; Apri Kurniasih (Universitas Muhammadiyah Tangerang, 2026)
This research is motivated by the importance of Quranic reading skills as a core competency and graduation standard for Integrated Islamic Schools (SKL JSIT) in Integrated Islamic-based schools; however, a gap in abilities among students was identified, where 60% of students were not yet able to read the Quran with tartil (measured recitation) and proper tajwid (rules of recitation). This study aims to determine the implementation of Intensive Tahsin Al-Quran Guidance in improving Quranic reading skills at SDIT Baitul Muslim, East Lampung. The research method used is Classroom Action Research (CAR) utilizing the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. Data collection was carried out through observations of learning activities, periodic oral tests of Quranic reading skills, interviews, and documentation. The subjects of this study were 25 students from the 3rd-grade Fatimah Az-Zahra class at SDIT Baitul Muslim. Data analysis was conducted using both descriptive qualitative and quantitative methods. The results showed that intensive tahsin Al-Quran guidance can be applied through the talaqqi and musyafahah methods (face-to-face and direct imitation), using small groups where one teacher guides 5–7 students. In the pre-cycle, only 40% of students could read the Quran with tartil and proper tajwid. In the first cycle, this increased to 68%. In the second cycle, it rose to 92%. Common errors such as reading fluency, makhraj (articulation points), ignorance of tajwid rules, and adab (etiquette) in reading the Quran were successfully minimized. In conclusion, structured and small-group intensive tahsin Al-Quran guidance is effective in correcting and improving the quality of Quranic recitation at SDIT Baitul Muslim, East Lampung. Keywords: Intensive Guidance, Quranic Reading Skills, Classroom Action Research.